PENGARUH KOMPETENSI TERHADAP KOMITMEN ORGANISASI PADA PERGURUAN TINGGI KEAGAMAAN ISLAM NEGERI DI INDONESIA TIMUR - Radlyah Hasan Jan; Faradila Hasan (Universitas Gorontalo, 2020)
This article talks about the effect of competence on organizational commitment in-state Islamic tertiary institutions in eastern Indonesia. The main purpose of this study is to find out how much employee competence affects organizational commitment. The approach used in this research is a quantitative approach. Based on the data that has been processed, the results of this study formulate that employee competence has a positive and significant effect on organizational commitment. So it can be concluded that to strengthen and increase organizational commitment in the State Islamic Religious College in Eastern Indonesia, an increase in the intensity of the application of employee competencies must be made.